Facility Siting in the Asia-Pacific : Perspectives on Knowledge Production and Application - Lam, Kin-che; Lesbirel, S. Hayden (Sidney Hayden), 1957-; Fung, Tung (Book collections on Project MUSE., 2013)
This volume addresses the management of conflicts that involve the siting of unwanted projects in the Asia-Pacific region. Contributors are renowned scholars in environmental policy and write from actual experience with the region, employing theoretical, comparative, and policy-based approaches to an analysis of environmental conflict, risk management, and public participation. The collection therefore will function as an invaluable resource for policymakers, environmentalists, and scholars of the Asia-Pacific and elsewhere.